2020
DOI: 10.12688/f1000research.24929.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of flow cytometric immuno-phenotyping of acute myeloid leukemia with minimal differentiation and acute T-cell lymphoblastic leukemia: A retrospective cross-sectional study

Abstract: Background: Acute leukemias (ALs) are a heterogeneous group of malignancies with various clinical, morphological, immunophenotypic, and molecular characteristics. Distinguishing between lymphoid and myeloid leukemia is often performed by flow cytometry. This study aimed to evaluate the immunophenotypic characterization and expression of immuno-markers in both acute myeloid leukemia (AML-M0) and acute T-cell lymphoblastic leukemia (T-ALL). Methods: A retrospective cross-sectional study was conducted in the Path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…In the present study 40.1% of T-ALL patients had aberrant expression including those with ETP-ALL. This was in accordance with Al-Saadi et al, (2020) who noted that 44.5% out of 45 T-ALL cases had aberrant phenotyes (72). Also Momani et al, (2016) found that out of 42 T-ALL cases, 28.6% showed aberrant antigen expression (16).…”
Section: Aberrant Expression In Patients With T-allsupporting
confidence: 84%
“…In the present study 40.1% of T-ALL patients had aberrant expression including those with ETP-ALL. This was in accordance with Al-Saadi et al, (2020) who noted that 44.5% out of 45 T-ALL cases had aberrant phenotyes (72). Also Momani et al, (2016) found that out of 42 T-ALL cases, 28.6% showed aberrant antigen expression (16).…”
Section: Aberrant Expression In Patients With T-allsupporting
confidence: 84%